Racial hierarchy and masculine space: Participatory in/equity in computational physics classrooms. Issue 3 (2nd July 2020) - Shah, Niral; Christensen, Julie A.; Ortiz, Nickolaus A.; Nguyen, Ai-Khanh; Byun, Sunghwan; Stroupe, David; Reinholz, Daniel L.
ABSTRACT: Background and Context: Computing is being integrated into a range of STEM disciplines. Still, computing remains inaccessible to many minoritized groups, especially girls and certain people of color. In this mixed methods study, we investigated racial and gendered patterns of equity and inequity in high school physics classrooms incorporating computational modeling, with an emphasis on group work. Objective: The objectives of this study were: 1) to document equity patterns in student participation and how they vary based on group composition by race and gender; and 2) to understand how discourses of race and gender influence group interactions. Method: We used the EQUIP web app (https://www.equip.ninja ) to analyze quantitative patterns in student participation. We then identified video of three group sessions and analyzed how discourses of race and gender mediated classroom interactions. Findings: Data show that racial hierarchies were prominent, with White students dominating group interaction and Black and Latinx students experiencing substantial marginalization. While there was evidence of gender equity in many groups – particularly those with greater proportions of girls – we show how computing and physics were still maintained as masculine spaces. Implications: Teachers of computing should intentionally structure learning environments to attenuate the impact of White supremacy and patriarchy. More research is also needed on how power operates in computing education at the level of classroom interaction.